The Effect of English Subtitle in English Video on Listening Comprehension - Firdausi, Lusi (Institut Agama Islam Tarbiyatut Tholabah, 2024)
The purpose of this study is to investigate the effect of the use of English subtitles in English videos on listening comprehension of English Education students in Muhammadiyah University of Jember by the year 2024. The research design used is Pre-experimental Design in the form of One-Group Pretest-Posttest Design. The researcher used SPSS 23 version software to facilitate the analysis of the data that was collected. The results obtained showed that there is an increase in the average score from the pre-test to the post-test. In paired-sample T-test, the result is 0.000 (smaller than 0.05). According to the results above, it can be noticed that the using of the same language text (in this case English) can be used as one of the recommendations in learning and teaching listening. However, it is still unclear how good the long-term effects are on learning, in terms of improved listening skills and vocabulary learning.